Demographic and clinical correlates of HIV-1 RNA levels in antiretroviral therapy-naive adults attending a tertiary hospital in Jos, Nigeria - Joseph Anejo-Okopi; Isaac Okoh Abah; Yakhat Barshep; Augustine Odo Ebonyi; Comfort Daniyam; Samson Ejiji Isa; Gomerep Simji; Stephen Oguche; Patricia Agaba; Patricia Lar; Oche Agbaji; John A. Idoko (Elsevier, 2017)
Background: Plasma HIV-RNA viral load (VL) of HIV-infected persons is an important prognostic factor in HIV management. We determined the VL among antiretroviral therapy (ART)-naive patients to identify the association between patients' demographic, clinical and laboratory characteristics with VL. Method: A cross-sectional study of 224 ART-naive HIV-1-infected patients (≥15 years of age) accessing care at the Jos University Teaching Hospital AIDS Prevention Initiative in Nigeria ART treatment centre, from October 2010 to April 2011. A log-linear model was used to determine if VL was related to demographic and clinical variables. Results: The patients had a median (interquartile range) age of 34 (28-41) years with females in the majority (59%). Females compared to males and pulmonary tuberculosis (PTB) co-infected compared to not co-infected patients had a significantly higher VL (14.9 loge versus 11.5 logeP=0.003 and 11.31 loge versus 11.89 logeP=0.047, respectively). VL tended to decrease with increasing CD4+ cell count levels in females, but remained relatively unchanged in males across all values of CD4+ cell counts. The difference (β) in the mean change in VL between males and females was loge 0.64 copies/mL, P=0.005. Conclusion: In ART-naive HIV-1-infected patients in our setting, females had significantly higher VL and lower CD4+ cell count, at the same VL threshold, compared to males, and hence were more likely to be at a higher risk of rapid progression to AIDS. Therefore, gender-based strategies for early identification and engaging females into care are required in this setting to mitigate against rapid progression to AIDS.